Ascorbic acid content in potato tubers with coloured flesh as affected by genotype, environment and storage - Karel HAMOUZ; David BEČKA; Ivana CAPOUCHOVÁ (Plant, Soil and Environment, 2018)
The aim of the study was to evaluate the effect of genotype, tuber flesh colour, site conditions, year of cultivation and storage on the content of ascorbic acid (AAC) in the tubers of twelve potato cultivars with coloured flesh, compared with the yellow-flesh cv. Agria. AAC ranged from 88.6 to 282.0 mg/kg fresh matter (FM) and it was significantly influenced by genotype. A significantly highest AAC, on a three-year average, was achieved by cv. Rosemarie with red flesh (218.9 mg/kg FM; 1.10-1.84-fold more than the other cultivars). Position number two was achieved by the control cv. Agria (199.4 mg/kg FM). The purple or red colour of the cultivars with coloured flesh did not have a significant effect on the AAC. A significantly higher (1.17 times) AAC was determined at the Uhříněves site with warmer climate and drier weather before the harvest, compared with the other site in Valečov. The AAC was also significantly affected by year of cultivation. Cold storage (4°C, 180 days) resulted in a significant decrease in AAC, which varied in dependence on the genotype of the cultivars (34.6% to 65.1%). However, no link to the colour of the tuber flesh was found.